The Rhetoric of Abolition: Continuity and Change in the Struggle Against America's Death Penalty, 1900-2010 - Cambra, Haley (2017)
This article seeks to understand when, how, and where the framing of arguments against capital punishment has changed. While others have focused exclusively on the national level, we studied the framing of abolitionist arguments in three American states: Connecticut, Kansas, and Texas. Each is located in a different region of the country, and each has its own distinctive death penalty history. We studied the framing of arguments against the death penalty from 1900 to 2010. Our study suggests that the rhetorical reframing of the campaign against capital punishment that has occurred at the national level has had deep resonance at the state level. Over the course of the 20th century in Connecticut, Kansas, and Texas, the focus on error and arbitrariness has assumed greater prominence among abolitionists. In each state, this change began to take hold in the late 1960s and 1970s and accelerated as the 20th century drew to its close. But, in each state, older frames persisted. Older arguments continued to occur with greater frequency than the new abolitionism